Identification and functional characterization of zebrafish K2P17.1 (TASK-4, TALK-2) two-pore-domain K+ channels - Staudacher, Ingo; Illg, Claudius; Gierten, Jakob; Seehausen, Sebastian; Schweizer, Patrick Alexander; Katus, Hugo; Thomas, Dierk (European journal of pharmacology, 2018)
Human K2P17.1 (TASK-4, TALK-2) two-pore-domain potassium (K2P) channels have recently been implicated in heart rhythm disorders including atrial fibrillation and conduction disease. The functional in vivo significance of K2P17.1 currents in cardiac electrophysiology remains incompletely understood. Danio rerio (zebrafish) may be utilized to elucidate the role of cardiac K2P channels in vivo. The aim of this work was to identify and characterize the zebrafish ortholog of K2P17.1 in comparison to its human counterpart. The zkcnk17 coding sequence was amplified from zebrafish cDNA. Zebrafish kcnk17 mRNA expression was assessed by polymerase chain reaction. Human and zebrafish K2P17.1 currents were analyzed using two-electrode voltage clamp electrophysiology and the Xenopus oocyte expression system. Kcnk17 mRNA was detected in zebrafish brain. Human and zebrafish K2P17.1 proteins exhibited 33.4% identity. Zebrafish K2P17.1 channels conducted K+ selective currents with open rectification properties. Both human and zebrafish K2P17.1 were inhibited by barium. In contrast to human K2P17.1, zK2P17.1 currents were not sensitive to extracellular alkalization, likely due to the lack of a lysine residue involved in pH sensing of hK2P17.1. In conclusion, zebrafish and human K2P17.1 channels display similar structural and regulatory properties. Zebrafish may serve as an in vivo model to study neuronal K2P17.1 function but does not appear appropriate for cardiac electrophysiology studies. Differences in pH sensitivity of zK2P17.1 currents need to be considered when zebrafish data are extrapolated to human physiology.
Gesehen am 21.04.2020
Im Titel ist "2P" in K2P13.1 tiefgestellt
Im Titel ist "+" in K+ hochgestellt